Degradation analysis of fuel cells for heavy-duty vehicle applications - Nyström, Emil; Olger, Emma; Sever, Stjepana; Stewall, Emelie (My University, 2023)
Climate change is one of the most pressing issues of today, and the emissions from fossil fuel-powered vehicles are major contributors. A potential solution to reduce the use of fossil fuels in vehicles is the implementation of fuel cells. However, the main challenge of using fuel cells is degradation, which results in a loss of performance. Therefore, on behalf of Volvo trucks, this project aims to model, analyze and draw conclusions about the performance and durability of a fuel cell used in trucks, with a special focus on the degradation in the catalyst layer caused by Ostwald ripening. The degradation is studied by modeling in Matlab and GT-Suite. The Matlab model studies the Ostwald ripening phenomena for two different drive cycles and outputs electrochemical surface area dependent on cell runtime. The data are then used to analyze the performance of a fuel cell stack in GT-Suite. The GT-Suite simulation calculates power output as well as polarization curves for the cell, which was done for each data point provided by the Matlab analysis. In relation to the Ostwald ripening phenomenon, a steady voltage displays a 17% loss of electrical power at 10 000 hours, in contrast, fluctuating voltage shows a 17% loss already at 6000 hours. It reveals a clear dependence on whether the voltage is steady or fluctuating. The study concludes that Ostwald ripening is a significant contributor to fuel cell degradation and needs to be taken into account for further development of the technology. Temperature and humidity have also been shown to ha an effect on fuel cell performance and need to be studied further in order for fuel cells to become a potential long-term solution for heavy-duty vehicles.
Keywords: Fuel cell; heavy-duty; degradation; Ostwald ripening phenomena